Clustering the agricultural SME sector in Eastern Highlands, Zimbabwe - Munyawarara, Ngoni; Govender, Krishna K (Goodwood Publishing, 2020)
Abstract Purpose: The clustering concept focuses on agricultural SME development. It is a strategy seeking to stimulate entrepreneurship growth and integrating broad SME structures that help to create value and competitiveness to enhance food security and community development in less developed countries. Research Methodology: This study investigated the impact of clustering the agricultural SME sector in Zimbabwe and it was restricted to the Eastern Highlands. The population consists of agricultural SMEs in Eastern Highlands. A methodological design survey on agricultural SME clusters was carried out using a purposive sampling technique, which selected a sample size with a total of 60 agricultural SMEs.An explanatory correlation analysis was used to analyze the data. Results: The study showed that clusters have a significant effect on agriculture SME the development in Zimbabwe. The study results indicated that clustering SMEs improve their competitiveness and market share growth, which is a rationale for economic growth. Findings also showed that clustering SMEs restructure their radical growth. These results further indicated that most agricultural SMEs are crippled due to a lack of cluster centers in their areas to enable them to compete and expand their market share Limitations: A solitary research tool seems to have weakened the study. Contribution: Clustering the agricultural Small and Medium Enterprises (SMEs) is very important because it promotes their competitiveness, productivity, market share, success, as well as community development and industrialization. Therefore this study contributed largely to the literature. Keywords: Clustering, Agricultural, SMEs, Community development, Food security